Writing the Orient: Johannes Schiltberger's Reisebuch (1394–1427) - Wolpert, F (2016)
This thesis is the first book-length study of Johannes Schiltberger’s Reisebuch, the German-language account of the Bavarian crusader’s approximately 30-year captivity and enforced travels in the Middle East under the Ottoman sultan Bayezid I (r. 1389–1403), the Turko-Mongolian warlord Timūr (r. 1370–1405) and his successors. It investigates the Reisebuch’s representation of the Orient. My reexamination of the manuscript and print transmission from c. 1450 to 1600 has shown that there were various versions of the Reisebuch in circulation, and I base my reading of the work on this basic multiplicity and variety. This variance is pertinent for a literary interpretation of the Reisebuch because the manifest narrative and material transformations go hand in hand with differing thematic foci, narratological and representational strategies, so that one can confidently contend each version of the Reisebuch negotiates a distinct relationship with the eastern ‘other’. I argue that the transmission diverges into three strands as (1) an abridged chronicle that emphasises the complexity of political and military relations in the East; (2) a proto-ethnographic account with a focus on religious diversity; and (3) six paratextual reconceptualisations of the Reisebuch as Turcica in early print. In short, my study engages with the transmission and transformation of material, on the one hand, and with the consequences of this creative process for cultural ideas, on the other: it asks what role ‘rewriting’ – deliberate and inventive adaptation – plays in the Reisebuch’s portrayals of the East. My thesis therefore provides not only the first in-depth reading of Schiltberger’s Reisebuch as a “medieval multi-text” (a term coined by Iain Macleod Higgins to indicate the inter-textuality and intra-textuality common to the medieval travel account) but highlights its representational process as multiple, polyvocal and dynamic.